Polymer‐derived Co2Si@SiC/C/SiOC/SiO2/Co3O4 nanoparticles: Microstructural evolution and enhanced EM absorbing properties. Issue 12 (11th June 2020) - Wu, Yongfeng; Zhong, Yunwang; Guan, Yan; Gu, Chong; Shao, Guangyu; Shi, Benyang; Su, Zhiming; Xu, Binbin; Yu, Zhaoju; Liu, Anhua
Abstract: In this work, porous core‐shell structured Co2 Si@SiC/C/SiOC/SiO2 /Co3 O4 nanoparticles were fabricated by a polymer‐derived ceramic approach. The in situ formation of mesopores on the shell, microstructural, and phase evolution of resulting nanoparticles were investigated in detail. The obtained nanoparticles‐paraffin composites possess a very low minimum reflection coefficient (RCmin ) −60.9 dB, broad effective absorption bandwidth 3.50 GHz in the X‐band and 15.5 GHz in the whole frequency range (from 2.5 to 18 GHz). The results indicate outstanding electromagnetic wave (EMW) absorbing performance among all the reported cobalt‐based nanomaterials, due to the reasons as follows: (a) The unique core‐shell structure as well as complex phase composition of SiC/C/SiOC/SiO2 /Co3 O4 in the shell, result in a large number of heterogeneous interfaces in the nanoparticles; (b) Nanoparticles have both dielectric and magnetic loss; (c) Mesopores in the shell prolong the propagation path of EMW, thereby increasing the absorption/reflection ratio of EMWs. Thanks to the material structure design, the resulting core‐shell structured cobalt‐containing ceramic nanoparticles have great potential for thin and high‐performance EMW absorbing materials applied in harsh environment. Abstract : Porous core‐shell structured cobalt‐containing ceramic nanoparticles: in‐situ formation of mesopores, microstructural evolution and enhanced EM absorbing properties.